Mortality and extraintestinal cancers in patients with primary sclerosing cholangitis and inflammatory bowel disease. (1st September 2014) - Ananthakrishnan, Ashwin N.; Cagan, Andrew; Gainer, Vivian S.; Cheng, Su-Chun; Cai, Tianxi; Szolovits, Peter; Shaw, Stanley Y.; Churchill, Susanne; Karlson, Elizabeth W.; Murphy, Shawn N.; Kohane, Isaac; Liao, Katherine P.
Abstract: Introduction: Primary sclerosing cholangitis (PSC) and inflammatory bowel disease (IBD) frequently co-occur. PSC is associated with increased risk for colorectal cancer (CRC). However, whether PSC is associated with increased risk of extraintestinal cancers or affects mortality in an IBD cohort has not been examined previously. Methods: In a multi-institutional IBD cohort of IBD, we established a diagnosis of PSC using a novel algorithm incorporating narrative and codified data with high positive and negative predictive value. Our primary outcome was occurrence of extraintestinal and digestive tract cancers. Mortality was determined through monthly linkage to the social security master death index. Results: In our cohort of 5506 patients with CD and 5522 patients with UC, a diagnosis of PSC was established in 224 patients (2%). Patients with IBD–PSC were younger and more likely to be male compared to IBD patients without PSC; three-quarters had UC. IBD–PSC patients had significantly increased overall risk of cancers compared to patients without PSC (OR 4.36, 95% CI 2.99–6.37). Analysis of specific cancer types revealed that a statistically significant excess risk for digestive tract cancer (OR 10.40, 95% CI 6.86–15.76), pancreatic cancer (OR 11.22, 95% CI 4.11–30.62), colorectal cancer (OR 5.00, 95% CI 2.80–8.95), and cholangiocarcinoma (OR 55.31, 95% CI 22.20–137.80) but not for other solid organ or hematologic malignancies. Conclusions: PSC is associated with increased risk of colorectal and pancreatobiliary cancer but not with excess risk of other solid organ cancers.